Direct-write 3D printing of UV-curable composites with continuous carbon fiber. (February 2023) - Abdullah, Arif M; Ding, Yuchen; He, Xu; Dunn, Martin; Yu, Kai
Continuous fiber-reinforced polymer composites, with their superior combinations of high stiffness, high strength, lightweight, and corrosion resistance, have been leading contenders in various applications ranging from aerospace to ground transportation. The integration with 3D printing allows the composite products to be customized quickly and fabricated inexpensively to meet unique specifications. However, the material-process-property relationships of 3D printed thermoset composites with continuous fiber are insufficiently explored in the field. In this work, a cost-effective 3D printing method is developed based on the direct ink writing method to print UV-curable composites reinforced with continuous carbon fiber. During the printing, the fiber tow is impregnated with an acrylate ink inside the printer head and then extruded onto the printer bed, where it is cured upon UV irradiation. The influences of different material and processing variables, such as the resin viscosity, nozzle size, printing speed, and substrate temperature, on the quality and mechanical properties of composites, are investigated. The porosity, stiffness, and strength of printed symmetric laminate are also examined. Finally, the 3D printing of composite structures and the conformal coating of curved surfaces along a defined printing path are demonstrated. The findings reported in this work could contribute to the rapid design and manufacturing of composite components with unprecedented mechanical properties and emerging functionalities for the automotive, defense, and aerospace industries.